Percutaneous cholecystostomy for delayed laparoscopic cholecystectomy in patients with acute cholecystitis: analysis of a single-centre experience and literature review - Erdinc Kamer; Fevzi Cengiz; Volkan Cakir; Omur Balli; Turan Acar; Mustafa Peskersoy; Mehmet Haciyanli (Gastroenterology Review)
Introduction : Percutaneous cholecystostomy (PC) has been used as a relatively safe and efficient temporising measure in the treatment of acute cholecystitis (AC) in high-risk patients with serious co-morbidity and in elderly patients. Aim : To assess the effectiveness, possible advantages, and complication of delayed laparoscopic cholecystectomy (LC) following PC in patients with AC. Material and methods : A total of 52 LC for AC were divided into two groups: the first group consisted of patients who had PC followed by LC (PCLC group, n = 12), and the second group consisted of patients who had conservative treatment followed by LC (non-PCLC group, n = 40). Eight of these patients were males and four were female. The groups were statistically compared regarding their demographic, comorbidity, hospital stay, conservation, and complication rates. PC was performed via the transhepatic route under ultrasound guidance using local anaesthesia. Results : Percutaneous cholecystostomy was technically successful in 12 patients with no attributable mortality or major complications. Upon the regression of cholecystitis and the decrease in APACHE-II scores, the PC catheter was unplugged and elective LC was scheduled for after 8 weeks. Ninety-two percent had complete resolution of symptoms within 48 h of intervention while 8% had partial resolution. All of the patients in PCLC and non-PCLC groups recovered well from cholecystectomy. Conclusions : This study suggests that PCLC would not significantly improve the outcome of LC as assessed by conversion and morbidity rate and hospital stay compared with non-PCLC. Percutaneous cholecystostomy is a valid alternative for patients with acute cholecystitis. And our study shows that the laparoscopic cholecystectomy is a good option in high-risk patients who have been treated by percutaneous cholecystostomy for acute cholecystitis.